Engagement with patients’ sexual problems: a comparative study among general practitioners and obstetrician-gynecologists - Aromaa, Anna; Kero, Katja; Manninen, Sanna-Mari; Vahlberg, Tero; Polo-Kantola, Päivi (Ovid Technologies (Wolters Kluwer Health), 2025)
Objectives: Even though good sexual health is an important part of well-being, the evaluation of patients' sexual problems is not necessarily routine for physicians. We compared engagement (attitudes, barriers to bringing up, and practice patterns) with patients' sexual problems among general practitioners (GPs) and obstetrician-gynecologists (OB/GYNs) with special regard for the sex and age of the physician.
Methods: A web-based questionnaire was used for data collection from 2 samples of physicians. The completed questionnaires from 402 GPs and 299 OB/GYNs were eligible for analysis. In the statistical analysis, the GPs were compared with the OB/GYNs as entire groups with multivariable binary logistic regression adjusted for sex and age. In addition, interaction and subgroup analysis by sex and age groups were both carried out.
Results: Both GPs and OB/GYNs considered treating sexual problems to be an important health care practice. However, compared with the OB/GYNs, the GPs were less likely to inquire about sexual problems during general medical history-taking [adjusted odds ratio (aOR): 0.23, 95% CI: 0.16-0.33, P < 0.0001] and more likely to consider diagnosing female sexual problems as being difficult (aOR: 2.44, 95% CI: 1.73-3.44, P < 0.0001). Compared with the OB/GYNs, the GPs were more likely to report having barriers - for example, "shortness of the appointment time"(aOR: 2.36, 95% CI: 1.53-3.63, P < 0.0001), "personal attitudes and beliefs"(aOR: 2.07, 95% CI: 1.41-3.67, P = 0.001), and "lack of knowledge about sexual medicine"(aOR: 2.05, 95% CI: 1.36-3.10, P = 0.001).
Conclusions: Both GPs and OB/GYNs considered the treatment of sexual problems to be an important health care practice; however, the engagement with patients' sexual problems among GPs was less structured.